Energy harvesting from wind and water for autonomous wireless sensor nodes - Azevedo, J.A.R. (2019)
It is well-known that wireless sensor networks (WSNs) promise to revolutionise the way the authors can interact with the physical world. However, the deployment of these systems in practical environments is very limited because of power constraints. Systems based on solar, vibrational and thermal energy are the most used in WSN applications and only a few studies consider the wind for energy harvesting. Another important source of energy is the water flow. In the context of the WSN, it was found that there are practically no systems using such source. The purpose of this study is to evaluate the use of small-scale wind and hydro generators for energy harvesting to power wireless sensor nodes. For this purpose, the power coefficients and the output power of several horizontal-axis and Savonius wind turbines were determined. Systems based on Pelton and propeller turbines were constructed to evaluate the effect of some parameters in small-scale power generation.